EXAMINING TOURISM RESILIENCE PRACTICES AS BASIS FOR A POST-COVID 19 RECOVERY IN THE PHILIPPINES - Era, Joy Sheelah Baraero; Del Rosario, Johncent Mendoza (Centre For Tourism Planning and Development, 2020)
This study examined the concepts and practices of tourism resilience vis-à-vis its vulnerability from shocks and external forces such as natural disasters, climate change, catastrophic events, and virus outbreaks (SARS, Ebola, and recently, the Corona Virus or COVID-19). Espousing a grounded perspective on resilience as emerging from this new phenomenon that is yet to be explored and analyzed, several studies and theories of tourism resilience were reviewed. These are: resilience cycle or ?Holling Loop?; the different types of resilience with an emphasis on adaptation and transformation; resilience as adaptation, anticipation, and preparedness from shocks. In addition, this study synthesized the different approaches of selected countries that already went through past virus outbreaks focusing on China, Taiwan, and Hong Kong?s post-SARS recovery actions, and the community resilience of Africa against the Ebola virus. From these literature reviews, insights were drawn for policy and planning considerations of the government and other stakeholders to adopt multi-level strategies that are sustainable, inclusive, adaptive, and innovative. Tourism recovery plans should also be centered on the solidarity of actions and resilience through systematic adaptation and transformation.